Requirements for a BIM Execution Plan (BEP) : a proposal for application in Colombia (2017)
The Architecture Engineering and Construction (AEC) Industry in Colombia is starting to implement Building Information Modeling (BIM) in their projects but in a much unorganized way. This issue could be attributed to a lack of standards and guidelines for the implementation along with the inexistent support to the industry from part of the government on the road to implementation. In this study 20 BIM Execution Plans (BEP) were reviewed searching for the presence of some subcomponents proposed by the authors in order to analyze which documents were more robust. Additionally, 5 in-depth interviews were conducted to AEC Colombian professionals from some of the industry main companies in order to identify problems in the BIM implementation that those companies were experiencing. Finally, a BEP template, which is a tool to implement BIM more organized in a project, was proposed using the documents analyzed and the problems identified in the interviews along with an explanation on how the information obtained was used to develop the new BEP template. Conclusions and recommendations are provided to enhance the BIM implementation in Colombia along with the template and the support files so every company that wishes to develop their own BEP can review the information presented on this paper.